2011
DOI: 10.1645/ge-2459.1
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism of Prehistoric Humans and Companion Animals from Antelope Cave, Mojave County, Northwest Arizona

Abstract: Previously, we reported a tick recovered from Antelope Cave in extreme northwest Arizona.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…Reviews of parasite evidence from New World archaeological sites show that zoonotic infections from wild reservoirs were diverse and common , Fugassa et al, 2011, Moore et al, 1969, Reinhard, 1990and Sianto et al, 2009). In addition, diverse flukes and tapeworms infected prehistoric Americans, varying across local resources and varied continental ecologies (Fry, 1977, Gonçalves et al, 2003, Reinhard, 1990, 1992aand Sianto et al, 2009.…”
Section: Diet and Parasitism In The New Worldmentioning
confidence: 99%
See 3 more Smart Citations
“…Reviews of parasite evidence from New World archaeological sites show that zoonotic infections from wild reservoirs were diverse and common , Fugassa et al, 2011, Moore et al, 1969, Reinhard, 1990and Sianto et al, 2009). In addition, diverse flukes and tapeworms infected prehistoric Americans, varying across local resources and varied continental ecologies (Fry, 1977, Gonçalves et al, 2003, Reinhard, 1990, 1992aand Sianto et al, 2009.…”
Section: Diet and Parasitism In The New Worldmentioning
confidence: 99%
“…Reinhard (1990) reviewed the many finds of acanthocephlans in Oregon, Utah and Colorado and concluded that these were true infections. Another thorny-headed worm genus, Macracanthorhynchus was recently reported (Fugassa et al, 2011;Jiménez et al, 2012). In this case, humans adapted by consuming a natural anthelmintic, sagebrush tea (Artemisia sp.)…”
Section: Diet and Parasitism In The New Worldmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the Acanthocephala and Heterakoidea species are not commonly found in humans, they may occasionally cause true infections in the human host. Interestingly, Acanthocephala eggs have been found at archaeological sites associated with humans (Fry & Hall 1969, Moore et al 1969, Fry 1970, Schmidt 1971, Ferreira et al 1989, Fugassa et al 2011. Parasites of the Acanthocephala phylum are primarily transmitted by the consumption of infected arthropods, which act as intermediate hosts (Moore et al 1969, Vicente et al 1997.…”
Section: Discussionmentioning
confidence: 99%